AtGCS promoter-driven clustered regularly interspaced short palindromic repeats/Cas9 highly efficiently generates homozygous/biallelic mutations in the transformed roots by Agrobacterium rhizogenes–mediated transformation - Liu, Shuang; Wang, Xiuyuan; Li, Qianqian; Peng, Wentao; Zhang, Zunmian; Chu, Pengfei; Guo, Shangjing; Fan, Yinglun; Lyu, Shanhua (Frontiers in Plant Science, 2022)
Agrobacterium rhizogenes-mediated (ARM) transformation provides a highly efficient and powerful tool to generate transgenic roots for studying root-related biology. For loss-of-function studies, transgenic roots induced indels mutation by CRISPR/Cas9 only with homozygous/ biallelic mutagenesis can exhibit mutant phenotype(s). However, a low frequency of homozygous mutants were produced by constitutive promoter to drive Cas9 expression. Here, we identified a highly efficient Arabidopsis thaliana gamma-glutamylcysteine synthetase promoter, termed AtGCSpro, indicated a strong activity in the region where will initiate root meristem and in the whole roots in broad eudicots species, and generated a higher homozygous/ biallelic mutation efficiency than the most widely used CaMV 35S promoter in driving Cas9 expression in soybean, Lotus japonicus, and tomato roots. By using pAtGCSpro-Cas9 system, an average homozygous/ biallelic mutation frequency is 1.7- and 8.3 fold higher than p2×35Spro-Cas9 system for single, and two target site(s) in the genome, respectively. Our results demonstrate the advantage of pAtGCSpro-Cas9 system used in ARM transformation, especially greatly potentially in diploid with multiple copy genes targeted mutations and polyploid plants with multiplex genome editing. AtGCSpro is conserved activity in various eudicots species which suggests that AtGCSpro might be dramatically potentially applied in a wide range of dicots.